BIBLIOMETRIC INSIGHTS INTO SPORTS MANAGEMENT RESEARCH AMONG STUDENTS: CURRENT TRENDS - Najib, Muhammad Luthfi; Fitri, Mustika; Paramitha, Sandey Tantra; Apriady, Hilmy (STKIP Singkawang, 2024)
Sports management among students in education has experienced rapid growth in its implementation. This article presents the current research trends on sport management in student research, through a bibliometric analysis of publication data from the top ten sport management. By reviewing 1260 articles from 2014 to 2024, this study examines the trends and progress in student sport management through bibliometric analysis. The purpose of this study is to understand the trends, focus and contribution of research in this field. Data were retrieved through Scopus and analyzed using bibliometric analysis, which reviews scientific publications related to student sport management. The VOSviewer tool was used to provide a visualization of the network collaboration between researchers, institutions and research subjects, which provides deeper insight into the information structure and dynamics of the field. This approach reveals long-term research trends, identifies key topics and highlights the contributions of institutions and key researchers. This study highlights the importance of ongoing research and collaboration in the development of sport management in students. In addition, a systematic observation of the literature was conducted to map potential future research directions based on current trends